Real Time Processing of Affective and Cognitive Stimuli in the Human Brain Extracted from MEG Signals - Ioannides, Andreas A.; Liu, Lichan; Theofilou, Dionyssios; Dammers, Jürgen; Burne, Tom; Ambler, TimAmbler; Rose, Steven (Brain topography, 2000)
The magnetoencephalography (MEG) signal was recorded while subjects watched a video containing separate blocks of affective and cognitive advertisements and recalled slides extracted from the video a day later. An earlier behavioural study using the same video material showed that the affective advertisements were better recalled and that administration of propranolol (a beta-adrenergic blocker) abolished this effect. Magnetic field tomography (MFT) was used to extract tomographic estimates of activity millisecond by millisecond from the continuous MEG signal. Statistically significant differences between affective and cognitive blocks were identified in posterior and prefrontal areas. Cognitive blocks produced stronger activity in posterior parietal areas and superior prefrontal cortex in all three subjects. Affective blocks modulated activity in orbitofrontal and retrosplenial cortex, amygdala and brainstem. Individual contributions to the statistical maps were traced in real time from milliseconds to many seconds. Time-locked responses from the recall session were used to compare average and single trial MFT solutions and to combine activations from all subjects into a common anatomical space. The last step produced statistically significant increases in occipital and inferior ventral cortex between 100 and 200 ms compared to a prestimulus baseline.